Assessing the PM2.5–O3 Correlation and Unraveling Their Drivers in Urban Environment: Insights from the Bohai Bay Region, China - Yan Nie; Yongxin Yan; Yuanyuan Ji; Rui Gao; Yanqin Ren; Fang Bi; Fanyi Shang; Jidong Li; Wanghui Chu; Hong Li (Atmosphere)
Understanding the correlation between PM2.5 and O3 is critical for complex air pollution control. This study comprehensively analyzed PM2.5 and O3 pollution characteristics, uncovered spatiotemporal variations in their correlation, and investigated the driving mechanisms of their association in Dongying, a typical petrochemical city in China’s Bohai Bay region. Results showed that PM2.5–O3 correlation in Dongying exhibited significant seasonal variations, spatial patterns, and concentration threshold effects from 2017 to 2023. PM2.5 and O3 showed strong positive correlations in summer, negative in winter, and weak positive in spring/autumn, with strongest links in western areas. The strongest positive PM2.5–O3 correlation occurred in summer when PM2.5 ≤ 35 μg·m−3 and O3 >160 μg·m−3, while the strongest negative correlation was exhibited in winter with PM2.5 > 75 μg·m−3 and O3 ≤ 100 μg·m−3. Meteorological conditions (T > 20 °C, RH < 30%, wind speed < 1.73 m/s, Ox > 125 μg·m−3) and non-sea-breeze periods enhanced the PM2.5–O3 positive correlation. During the four typical pollution episodes, the positive PM2.5–O3 correlation in summer was propelled by synchronous increases in O3 and secondary components via shared precursors. In autumn, strong positivity resulted from secondary component–O3 correlations (r > 0.7) and dominance of secondary formation in PM2.5. In winter, the negative correlation stemmed from primary emissions inhibiting photochemistry. Random forest analysis showed that Ox, RH, and T drove positive PM2.5–O3 correlation via photochemistry in summer, whereas winter primary emissions and NO titration caused negative correlation. This study offers guidance for the collaborative PM2.5 and O3 control in the petrochemical cities of the Bay region.